Estimating the Stability of Orthodontic Micro-implant after Applying Orthodontic Force "An Experimental in Vivo Study" - Khudair A Al-Jumaili; Saba H Al-Zubaidi; Mohammad S Suleiman (Al-Rafidain Dental Journal, 2013)
Aims: To evaluate weather micro-screw implants remain stationary or move against orthodontic forces during different healing periods (immediate loading, loading after 2 weeks and 4 weeks). Materials and Methods: Thirty micro-screw implants were implanted in 6 rabbits. These rabbits divided into 3 groups (2 in each group). The first group received loading immediaty after implantation. The second and third groups received loading after 2 weeks and 4 weeks of healing period respectively. The stability of these implants was measured using periotest device before and after loading. The data was ana-lyzed using descriptive statistic, Analysis of variance (ANOVA), Duncan Multiple analysis range test and student t-test. Result: Among the three groups, the first group having a significant greater stability of micro-screw implants immediately before and after loading and after 2 weeks of loading period. Conclusion: micro-screw implants can be loaded immediately after implantation with light orthodontic force; also these implants can be loaded after 4 weeks of healing period.